Pelatihan dan Pendampingan Pemasaran Digital dengan Teknik Storytelling untuk Komunitas UMKM Teras Ciapus - Pratiwi, Aprilianti; Gati Dwi Yuliana; Basar Ananta Farrel Silitonga; Risma Amalia Ulfa Dewi (Institut Nalanda, 2025)
The purpose of this community service is to improve digital marketing knowledge and skills, especially through storytelling techniques or product narratives from members of the Teras Ciapus Mandiri community, Tamansari District, Bogor Regency, West Java. The method carried out in this activity is training and assisting digital marketing with storytelling techniques. The training activities were carried out face-to-face which was attended by 10 participants. Then it was continued with hybrid mentoring activities for two months, namely from September to November 2024. The results of training and mentoring activities showed a significant increase in participants' understanding and digital marketing practices. This can be seen from the increase in post-test scores compared to pre-tests. Participants also experienced an increase in sales, variations of promotional content, and interactions on social media based on the evaluation conducted by the team. This training recommends the use of a weekly content calendar to improve the consistency and effectiveness of product promotions.